Association between Diabetes Complications and the Triglyceride-Glucose Index in Hospitalized Patients with Type 2 Diabetes - Ying Pan; Shao Zhong; Kaixin Zhou; Zijian Tian; Fei Chen; Ziqing Liu; Zhaoxu Geng; Shaoyun Li; Rong Huang; Heyou Wang; Weiqing Zou; Ji Hu (Journal of Diabetes Research)
Background. Triglyceride-glucose (TyG) index is a convenient indicator of insulin resistance. It has been shown to be associated with macrovascular and microvascular complications in nonhospitalized diabetic patients. However, whether TyG index is a risk factor of diabetes vascular complications in hospitalized type 2 diabetic patients is unclear. We sought to explore the association between TyG index and the risk of macrovascular and microvascular complications in a large Chinese cohort of hospitalized patients. Method. A total of 4,721 patients with type 2 diabetes (T2D) who were hospitalized in the Department of Endocrinology, Kunshan Hospital Affiliated to Jiangsu University were enrolled between January 2015 and November 2020. TyG index was calculated as lnfasting triglycerides mg/dL×fasting glucose mg/dL/2. Measures of macrovascular complications included brachial-ankle pulse wave velocity (ba-PWV) and ankle-brachial index (ABI), whilst urine microalbumin (MAU), chronic kidney disease (CKD), and diabetic retinopathy (DR) were evaluated for microvascular complications. Logistic regressions were used to examine the association between TyG index and diabetes complications. Results. In univariate logistic regressions, higher TyG index was significantly (p<0.002) associated with increased odds of MAU (OR=1.39, 95% CI: [1.22~1.59]) and ABI (OR=1.31, 95% CI: [1.10-1.57]) but not CKD, DR, or ba-PWV. After controlling for confounders such as age, sex, and body mass index (BMI), TyG index remained strongly (p<0.002) associated with MAU and ABI. These associations were more pronounced (p<0.001) in patients with poor glycemic control or in the elderly. Conclusion. Hospitalized patients with an elevated TyG index were at a higher risk of lower limb vascular stenosis and nephric microvascular damage. Close monitoring of TyG index in patients with younger age or poor glycemic control could potentially reduce the burden of diabetes complications and prevent readmission.